(untitled) (Scientific journal of the Fergana State University, 2023)
The article summarizes the need for serious linguistic analysis of medical terms, both quantitatively and qualitatively, and their study from a structural-semantic point of view has become not only one of the current trends in modern terminology, but also one of the most pressing issues of modern terminology.